Limitations and usefulness of biopsy techniques for the diagnosis of metastatic bone and soft tissue tumors. (August 2021) - Hashimoto, Kazuhiko; Nishimura, Shunji; Ito, Tomohiko; Oka, Naohiro; Akagi, Masao
Abstract: Background: Biopsies are widely used for diagnosing metastatic tumors in the bone and soft tissues; however, their usefulness and limitations remain unclear. Patients and methods: Biopsies of patients (13 men, 8 women, mean age 76 years) with metastatic tumors in the bone (19 patients) and soft tissues (2 patients) were reviewed retrospectively. Investigators surveyed the lesion sites, medical histories, Eastern Cooperative Oncology Group (ECOG) Performance Status (PS), biopsy sites, methods, comorbidities, diagnoses, treatments, and outcomes. Results: Five patients had multiple lesions, and 16 patients had one lesion. The ECOG PS scores were PS0 (11 patients), PS1 (7 patients), PS2 (2 patients), and PS3 (1 patient). Biopsy sites included pelvic bone (6 cases), rib bone (5 cases), spinal vertebra (7 cases), soft tissue of the shoulder (2 cases), and inner retroperitoneum (1 case). Diagnostic methods included open biopsy (8 patients), core needle biopsy under general (7 patients) or local (3 patients) anesthesia, and computed tomography–guided core needle biopsy under local anesthesia (3 patients). Histology indicated hematological malignancies (9 cases); breast cancer (3 patients); lung cancer, renal cell cancer, cancer of unknown primary (2 cases each); prostate cancer, endometrial (uterine) cancer, and myxoid liposarcoma (1 case each). The primary site identification rate was 90.5%. Outcomes included three patients "dead of disease." Conclusion: Biopsies are useful for early diagnosis and for the scrutiny of primary lesions of metastatic bone and soft tissue tumors. If the primary tumor is still unknown after biopsy, evidence-based treatment should be initiated promptly. Highlights: 1. Biopsy is essential and useful for the close examination of metastatic bone and soft tissue tumors. It is better to use minimally invasive biopsy methods and biopsy sites. For cancers of unknown primary, the primary site can be identified by tracing the patient's history.